2011
DOI: 10.1007/s00249-011-0712-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the interceptor action of caffeine on the in vitro biological effect of the anti-tumour agent topotecan

Abstract: Using published in vitro data on the dependence of the percentage of apoptosis induced by the anti-cancer drug topotecan in a leukaemia cell line on the concentration of added caffeine, and a general model of competitive binding in a system containing two aromatic drugs and DNA, it has been shown to be possible to quantify the relative change in the biological effect just using a set of component concentrations and equilibrium constants of the complexation of the drugs. It is also proposed that a general model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…These features enable us to draw a parallel with the well-investigated drug-xanthine systems (Buchelnikov et al 2012;Evstigneev et al 2006Evstigneev et al , 2008Evstigneev et al , 2011Evstign eev 2010Evstign eev , 2013Goluriski et al 2013;Larsen et al 1996;Piosik et al 2010;Traganos et al 1991;Woziwodzka et al 2011), for which similar effects are observed on joint in vitro action of aromatic BACs. Of particular importance here is that in the drug-xanthine systems, the operation of the interceptor mechanism (i.e., the drugxanthine hetero-association) can be considered as widely accepted.…”
Section: Drug Action In the Presence Of C6fl Fullerenementioning
confidence: 93%
See 4 more Smart Citations
“…These features enable us to draw a parallel with the well-investigated drug-xanthine systems (Buchelnikov et al 2012;Evstigneev et al 2006Evstigneev et al , 2008Evstigneev et al , 2011Evstign eev 2010Evstign eev , 2013Goluriski et al 2013;Larsen et al 1996;Piosik et al 2010;Traganos et al 1991;Woziwodzka et al 2011), for which similar effects are observed on joint in vitro action of aromatic BACs. Of particular importance here is that in the drug-xanthine systems, the operation of the interceptor mechanism (i.e., the drugxanthine hetero-association) can be considered as widely accepted.…”
Section: Drug Action In the Presence Of C6fl Fullerenementioning
confidence: 93%
“…Unfortunately, identification of the role of the interceptor mechanism directly at the cellular level is not possible, and in similar works available in the lit erature, the conclusions about its significance are com monly made on the basis of either the fact of an effective drug-interceptor hetero-association (Piosik et al 2010;Traganos et al 1991;Woziwodzka et al 2011), or the ability to describe in vitro data within the framework of the theory of interceptor/protector action (Buchelnikov et al 2012;Evstigneev et al 2008Evstigneev et al , 2011Evstigneev 2010). The existence of an effective hetero-association in the drug-fullerene systems has been shown previously , and the degree of correspond ence of the parameters measured in the present work (HGQ, ENN) with the theory of interceptor/protector action was investigated in order to gain further under standing of the role of the interceptor mechanism in the biological effects observed (see Fig.…”
Section: Drug Action In the Presence Of C6fl Fullerenementioning
confidence: 99%
See 3 more Smart Citations